Work Engagement sebagai Prediktor Kinerja pada Kurir di Bujang Kurir Pontianak - Febriyanti, Nindy; Ramadhan, Riszky; Fitlya, Rizki (Jurnal Ilmiah Psyche, 2025)
The success of a company depends heavily on the performance of its human resources. Therefore, it is crucial to ensure that employees have a sense of connection to their work and the company, often referred to as work engagement. Work engagement plays a role in encouraging employees to contribute their best to their work, as employees who are engaged tend to be passionate, enthusiastic, and committed to achieving company goals. The primary objective of this study is to determine how work engagement affects the performance of couriers at Bujang Kurir Pontianak. Using quantitative methods, this study collected data through a psychological scale that measures the performance and work engagement of couriers in the workplace. The research subjects consisted of 30 respondents, representing the entire population. They were selected by employing a saturated sampling technique, in which all members of the population were the subjects of the study. The analysis results based on a simple linear regression test indicate that work engagement has a significant effect on performance. The significance value is 0.001 (p <0.05) indicates that work engagement significantly improves performance. With a coefficient of determination (R²) of 0.617, work engagement contributes 61.7% to performance, while the remainder is affected by other contributing factors. Thus, increasing work engagement can directly improve performance.